An exploration of the self-perceived nutrition competencies of pharmacists - Dervla Kelly; Jacqueline Chawke; Megan Keane; Helen Conway; Pauline Douglas; Anne Griffin (Elsevier, 2022)
Background: Pharmacists are integral members of healthcare teams, providing accessible nutrition care to patients, carers and health professionals. However, little is known about nutrition competence among pharmacists. Objective: The aim of the study is to determine the self-perceived competence in providing nutrition care among pharmacists in Ireland. Methods: This cross-sectional study used a mixed methods design consisting of an online survey delivered to pharmacists in Ireland. The pharmacists' self-perceived competencies according to confidence in knowledge, skills, communication and counselling, and attitudes in nutrition care were assessed using the validated NUTCOMP questionnaire. Qualitative responses in relation to nutrition knowledge were also gathered. Questionnaire responses were analysed using descriptive statistics and free text narratives were coded into themes and subthemes. Results: A total of n = 557 (74% (n = 413) female; 24.1% (n = 134) male) respondents completed the questionnaire providing a 14.9% response rate. Confidence in nutrition knowledge (mean score (SD) 21.6 (±4.31) out of a maximum of 35 points), nutrition skills (mean score (SD) 31.8 (±7.74) out of a maximum count of 55) and nutrition related counselling and communication (mean score (SD) 29.8 (±6.35) out of a maximum of 45 points) were limited. Most respondents had completed a programme with some nutrition content (60.8%) either formally or informally. Previous nutrition education was positively associated with greater scores in knowledge, skills, communication/counselling and attitudes towards nutrition care (p = ≤0.001). Over three-quarters of respondents (78.1%) agreed that they would like further nutrition education to support themselves in their roles as pharmacists. Thematic analysis highlights the role of interprofessional nutrition care, barriers to providing nutritional care in practice and opportunities for improving nutrition training. Conclusions: Most pharmacists reported being somewhat confident in their nutrition knowledge, skills and attitudes and are willing to participate in further nutrition education to support their patients. The findings suggest that there are other barriers to providing nutrition care in the pharmacy setting such as time, renumeration and lack of community dietitians.